(517) Some Remarks on the Problem of Pricing in the Socialist Economy بعض الملاحظات حول مشكلة التسعير في الاقتصاد الاشتراكي - Fedorowicz, Zdzislaw (INP, 2024)
Remarks on Price Policy in the Socialist Economy, the pricing policy in a socialist economy is based on two fundamental principles: Relationship Between Prices, Wages, and Investment: The first principle establishes the necessary connections between the prices of consumption goods and nominal wages, as well as between the prices of investment goods and the amount of investment funds, primarily derived from the gross profits of socialist enterprises. Covering Production Costs Through Prices: The second principle ensures that prices cover production costs, securing the financial independence of producers and enabling efficient economic calculations for production and investments. This pricing policy framework provides sufficient flexibility to establish different relationships between the prices of various goods, such as consumption commodities and production goods. These limits can be analyzed through a simple model of a socialist economy, which includes two productive sectors (Sector I producing production means, and Sector II producing consumption goods), individual consumers earning wages, and a state budget accumulating funds for investments and collective consumption